2023
DOI: 10.3389/fgwh.2022.1032592
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the utilization and outcomes of endovascular treatment after acute ischemic stroke: A systematic review and meta-analysis

Abstract: BackgroundStudies of sex differences in the use and outcomes of endovascular treatment (EVT) for acute ischemic stroke report inconsistent resultsMethodsWe systematically searched PubMed and Embase databases for studies examining sex-specific utilization of EVT for acute ischemic stroke published before 31 December 2021. Estimates were compared by study type: randomized clinical trials (RCTs) and non-RCTs (hospital-based, registry-based or administrative data). Random effects odds ratios (ORs) were generated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
2
0
1
Order By: Relevance
“…39 The opposite is true for thrombectomy, from which females benefit more in achieving better functional outcome, although other studies found no notable sex differences in the outcome of stroke after thrombectomy. 47 This study found that in patients aged 80 and older, a higher proportion of stroke patients were females. Females were older at the time of onset and suffered from more severe strokes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…39 The opposite is true for thrombectomy, from which females benefit more in achieving better functional outcome, although other studies found no notable sex differences in the outcome of stroke after thrombectomy. 47 This study found that in patients aged 80 and older, a higher proportion of stroke patients were females. Females were older at the time of onset and suffered from more severe strokes.…”
Section: Discussionmentioning
confidence: 77%
“…The authors attributed this to the more flexible dosing of IAT and the higher concentrations of fibrinolytic agent achieved, which could potentially overcome the thrombolytic resistance of females 39 . The opposite is true for thrombectomy, from which females benefit more in achieving better functional outcome, although other studies found no notable sex differences in the outcome of stroke after thrombectomy 47 …”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на значительные различия в результатах отдельных исследований, объединенные данные показывают, что женщинам с острым инсультом внутривенный тромболизис назначают реже, чем мужчинам [64]. Недавний систематический обзор в целом не выявил половых различий в частоте использования эндоваскулярной терапии или ее исходах, но с разницей между отдельными странами [65]. Появляющиеся данные свидетельствуют о том, что женщины имеют больше пользы от вмешательства, чем мужчины, но это преимущество используется не в полной мере.…”
Section: результатыunclassified